The history of political conflicts in Zimbabwe: The history of political conflicts in Zimbabwe (Journal of the College of Education for Women, 2019)
AbstractThis research shows the history of political conflicts in Zimbabwe, themerits of the political struggle for power in this country since the Britishcolonial period, especially after the British administration announced thatZimbabwe is a local colony of the British Crown in 1923, as the settlementprocess against the wide white deprive local people to own and lease landand low income, as well as the 1961 Constitution, which granted access tothe white powers in accordance with the authority of the top menu for theexisting lower allocated to blacks.These events and factors led to a national rejection in Zimbabwe,which crystallized in the form of parties and political organizations through thetwo major parties: Zimbabwe African People's Union (ZAPU) led by JoshuaNkomo, and African National Union (ZANU), led by Robert Mugabe.The features of political struggles for power started in Zimbabweduring the elections in 1962 which made the whites (50) seats guaranteed tothem by the Constitution, and deprived blacks of those seats, a matter whichled the national leadership to engage with the government's white led by (IanSmith) in long discussions of settlement of this question which ended with theexpulsion of the country's native citizins from the local authority for ever. Thatphase had revealed the dimensions of the struggle for power that was limitedbetween white settlers and national leaders.But after independence, especially after the elections of 1979 whichallocated (80) seats for the local population, compared to (20) seats for whitesand the formation of the first black majority government in the country, thefeatures of another struggle for power between nationalists themselvesappeared, as the outcomes of the elections in 1979 which did not satisfysome of them and led bishop Mozhuiroa to establish a new party known asthe African National Council party which won the elections, But this led toquestion the legitimacy of the elections and declared a state of civildisobedience to that government, and repeat the elections in which RobertMugabe won in 1980, ending by that the phase of the conflict.The phase of cohabitation between the national party (ZAPU) and(ZANU) came to an end, with Mugabe's reach to power after he has declareda one-party politics, which made it more powerful than the first, especiallyafter the deportation of some his rivals, like Joshua Nkomo outside thecountry, the liquidation of other rivals, and the declaration of the presidentialsystem in the country.In 2000, another phase of power struggle appeared with theemergence of a new opposition against the rule of Mugabe, under the nameof the movement for Democratic Change, which compete with Mugabe in theelections of 2002, and elections of 2008, an issue which has raised a bigstorm in the country, ended after the intervention of some African leaders withMugabe's concession the opposition as a partner in government after hechanged the form of political regime in Zimbabwe from presidential toparliamentary, he stayed as the President of the Republic while the leader ofthe opposition (Morgan Tsvangirai) became the Chairman of the Zimbabweangovernment.